In silico analysis of single nucleotide polymorphism (SNPs) in human [BMPR2] gene - Mohamed, Mohamed Saeed Elhassan; Elnasri, Hind AbdelAziz; Elbakri, Afraa Mohamed; Khaeir, Mona Abdelrahman Mohamed. (Journal of agricultural, environmental and veterinary sciences, 2019)
Background: (BMPR2) gene is encoded gene and cause pulmonary arterial hypertension. Also, it has major role in regulating the growth the maturation of cells. A (BMPR2) gene contains only 25 SNPs as deleterious SNPs and was analyzed in this study. Material and methods: 25 SNPs investigated using the NCBI database (htt: / / www.ncbi.nlm.nih.gov/)and the SNPs were analyzed using six prediction tools: SIFT, Polyphen- 2, I- Mutant, PROVEAN, PhD- SNP and Project Hope. 76% SNPs predict Probably Damaging by POLYPHEN software. the protein stability checked by I- MUTANT and 72% SNPs trend to decrease effected. when used SNPs & GO 52% SNPs were diseased.64% SNPs were deleterious by PROVEAN. There are 20 associated genes, 14 genes share the same protein domains and 13 genes similar in their expression when predicted by GENE MANIA software. Using PROJEC HOPE software to predict the structural effect in function. Result: eight SNPs of 25 SNPs were sharing the same and significant results, so that leads to confirm this result. Conclusions: eight SNPs, rs137852744, rs137852745, rs137852746, rs137852749, rs137852750, rs137852750, rs143740797and rs374694591 were shown to have highly damaging and cause the pulmonary arterial hypertension disease.